2022
DOI: 10.48550/arxiv.2201.00988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topological Anderson insulators with different bulk states in quasiperiodic chains

Ling-Zhi Tang,
Shu-Na Liu,
Guo-Qing Zhang
et al.

Abstract: We investigate the topology and localization of one-dimensional Hermitian and non-Hermitian Su-Schrieffer-Heeger chains with quasiperiodic hopping modulations. In the Hermitian case, phase diagrams are obtained by numerically and analytically calculating various topological and localization characters. We show the presence of topological extended, intermediate, and localized phases due to the coexistence of topological and localization phase transitions driven by the quasiperiodic disorder. In particular, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Note added: on submission of this manuscript, we notice a very recent preprint arXiv:2201:00988 entitled "Topological Anderson insulators with different bulk states in quasiperiodic chains". [65] The authors studied a similar problem, and main results of the TAI regime with the intermediate phase were obtained. In this paper, we derive the exact expression of mobility edges in this TAI phase.…”
Section: Discussionmentioning
confidence: 99%
“…Note added: on submission of this manuscript, we notice a very recent preprint arXiv:2201:00988 entitled "Topological Anderson insulators with different bulk states in quasiperiodic chains". [65] The authors studied a similar problem, and main results of the TAI regime with the intermediate phase were obtained. In this paper, we derive the exact expression of mobility edges in this TAI phase.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TAIs are induced by the uncorrelated disorders in these studies. For instance, both uncorrelated random [26] and quasiperiodic disorders [57][58][59] can give rise to the TAI phase in 1D Su-Schrieffer-Heeger (SSH) chains. It was shown that the spatial correlations in the disorder can entirely suppress the emergence of the TAI phase on two-dimensional quantum spin Hall systems with Gaussian correlated onsite potentials [60].…”
Section: Introductionmentioning
confidence: 99%